Lei 13.465/2017: um caminho para a privatização de bens comuns? - Alflen, Jessica (2020)
The present work intended to develop an analysis proposal regarding the impacts of new Land Regularization Law (13,465/2017), with the main objective of ascertaining whether the mentioned law, contrary to the objectives of the institute of land regularization, aims or not, in fact, promote a liquidation of public assets, through privatization veiled public goods located in the Brazilian coastal zone, causing damage to common goods. Thus, the study guide intended to analyze the legal regime of public goods, in Brazilian legislation and doctrine, seeking to outline a concept and characteristic of these goods, in addition to of having intended to demarcate a definition of common goods, outside the public-private rhetoric, also presenting a notion of the use, management and protection of common goods, which, Historically, they have always involved major social and economic conflicts. Right away, we sought to outline the definition and delimitation of the Brazilian coastal zone, presenting some considerations about its management and protection, noting that it is part of the conception of common goods. Finally, the occupation process in coastal areas was investigated, with the its accelerated urbanization process gave rise to the need for land regularization, which gained a new legislative framework, with the promulgation of Law 13,465/2017. In this way, the Based on the analysis of the elements presented, it can be concluded that Law 13,465/2017, published under the cynical argument of land regularization, to promote development economic situation in the country, represents a tendency towards privatization of public goods, and therefore therefore, of the common goods, without any public dialogue and popular participation regarding the question. Thus, the aforementioned law represents a major setback. Based on the momentum of privatization of public assets, Law 13,465/2017, intends to attribute private property, previously public areas, thus preventing the population's free access to these goods. You The objectives of this study were achieved through the hypothetical-deductive method. The method of procedure used was the monograph, and, as an instrument for carrying out the process investigative, documentary and bibliographic techniques were used.